2016
DOI: 10.15389/agrobiology.2016.6.912eng
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in Combination With Amino Acids Change Productive and Immunological Indicators of Broiler Chicken

Abstract: A b s t r a c tThe prospects of using metal nanoparticles to stimulate productivity of farm animals are widely discussed. However, nano-sized materials exhibit various negative properties, such as prooxidant effects, and can provoke apoptosis and kidney damage. A possible approach is the use of ultrafine materials in combination with agents leveling adverse effects of nanoparticles. For the first time we studied the prospects of joint use of iron and arginine nanoparticles, the mechanism of their interaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
1
Order By: Relevance
“…Animal feeding is closely related to the meat/fish processing industry. Yausheva et al (2016) showed that the joint utilization of iron nanoparticles and arginine raised weight gain by up to 9.2% in poultry as compared to the control, and, moreover, iron nanoparticles together with a mixture of amino acids (arginine, lysine, and methionine) provided an increase of up to 20%.…”
Section: Non-encapsulating Nanoparticlesmentioning
confidence: 97%
“…Animal feeding is closely related to the meat/fish processing industry. Yausheva et al (2016) showed that the joint utilization of iron nanoparticles and arginine raised weight gain by up to 9.2% in poultry as compared to the control, and, moreover, iron nanoparticles together with a mixture of amino acids (arginine, lysine, and methionine) provided an increase of up to 20%.…”
Section: Non-encapsulating Nanoparticlesmentioning
confidence: 97%
“…При этом большое значение придается наноматериалам как перспективным компонентам рациона животных [5]. Препараты металлических наночастиц находят все более широкое применение в качестве источников микроэлементов [6] и различных добавок [7], для повышения иммунитета животных [8], а также в качестве стимулирующих рост антибиотиков [9]. Это определяет необходимость изучения косвенного воздействия наноматериалов на гомеостаз сельскохозяйственных животных и птицы и кишечную микробиоту [10].…”
Section: частная зоотехния кормление животныхunclassified
“…The results of earlier studies indicate the pronounced biological effect of these compounds in low concentrations without manifestations of toxic reaction in the body of rats (Dolaychuk et al, 2015;Fedoruk at al., 2018) and cows, pigs, rabbits, bees (Iskra et al, 2017;Malavolta & Mocchegiani, 2018). Studies by other authors (Mohapatra et al, 2014;Yausheva et al, 2016;Landry et al, 2017) stipulate a stimulating metabolic effect of nanosized compounds of biotic mineral elements. Adequate physiological ratios of I, Se, Cr, Ge citrates, for their combined use in laboratory animals were experimentally determined (Dolaychuk et al, 2015;Iskra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding mature, 4-8-month-old, rats (feeding started at 4 months and lasted till the end of the 8 th month) and young, 0-4-monthold, rats (feeding started at birth and lasted for 4 months) with "nanoaquacitrates" of germanium, chromium, and selenium causes an increase of physiological reactivity in their bodies (Dolaychuk et al, 2015). The study of the biological activity of new derivatives of organic compounds I, Se, S, including those obtained on the basis of nanotechnology, indicates their high physiological activity (Yausheva et al, 2016;Iskra et al, 2017;Stoika et al, 2017). Environmental considerations and regulations limiting trace mineral supply and improvements in analytical methods to detect putative contaminants in mineral sources have led to a need for a re-examination of trace mineral requirements.…”
Section: Introductionmentioning
confidence: 99%